PENGARUH PSYCHOLOGYCAL CAPITAL DAN MOTIVASI TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI - Sawali Murdiono, 12.5202.0113; Fauzan, Moh (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimstoanalyzethe influence of"The Effect ofCapitalPsychologycalandMotivation onOrganizational CulturemoderatedTeacherPerformance". Inthis studypopulation ofallprimary schoolteachers in the DistrictTersono, whereassamples takenas many as 165peopleasrespondentsto thecensustechnique. Byall thecriteria ofpublic servantsinthe DistrictEducation OfficeTersono. Measurementsusing5Likert scale(seven) alternative answers. Testinstrumentsused arevalidity and reliability. While thetestmodel usedisthe coefficientof determinationandF test(goodnes of Fit). Testthis hypothesisusingregressionanalysis.The results ofthe studycan be summarized asfollows: (i) PsychologicalCapitalis notimpactonteacher performance, (ii) Work Motivationis notimpactonteacher performance, (iii) Organizationalculture hasÂ  impactÂ  on teacher performance, (iv)Organizationalcultureis not moderates impact ofPsychologicalCapitalon the Performance ofTeachers, (iv) Organizational Culture is not moderates impact of Motivationonteacher performance. Keywords:PsychologicalCapital, Motivation, Organizational Cultureand Teachers Performance.